The Influence of Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation, and Price Value on Students’ Behavioral Intention to Use Online Courses at Universitas Negeri Jakarta - Tasha Dwi Oktora; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research investigates the determinants of undergraduate students’ behavioural intention to adopt online courses at Universitas Negeri Jakarta (UNJ) through the UTAUT2 framework. Using PLS-SEM, data from 128 respondents were analysed to analyze all variables emerges as the most influential factor, followed by Hedonic Motivation, whereas the remaining constructs do not have a significant effect. The model accounts for 40.2% of the variance in behavioural intention. Overall, the results suggest that students’ engagement with online courses is shaped more by considerations of cost and enjoyment than by perceived usefulness or social pressure, offering valuable insights for the design and improvement of online learning platforms in the post-pandemic context.